Does Digital Financial Inclusion Affect Economic Development and the Environment differently? Evidence from India Using Robust Least Square Model (Global Journal of Human-Social Science, 2025)
This study employs a Robust Least Squares Regression model to examine the effects of digital financial inclusion (FI) on economic development and environmental quality in India from 2004 to 2023. The study focuses on how better access to financial resources through digital financial inclusion is essential for both economic growth and poverty reduction. The positive relationship between GDP and digital financial inclusion is emphasized in this research, supported by strong statistical evidence, including a high R-squared value that shows the independent variables significantly influence GDP variability. The study also examines the potential environmental impacts of increased financial inclusion, noting that while it may stimulate economic growth, it may also lead to increased pollution and energy consumption.